Improved uniformity of xanthan gum resistive memory device by lowering activation energy. (1st April 2023) - Chang, Yu-Chi; Liu, Hao-Jung; Chang, Yu-Min; Huang, Hui-Shin; Chen, Yu-Ling
Abstract: In this study, the dielectric layer of the xanthan gum resistive memory is treated by air plasma. Compared with the untreated original device, when the device is treated with plasma for 30 s, the activation energy is reduced from 0.17 to 0.13 eV, which helps to control the randomness of the path of trap hopping conduction. Thus, the average set voltage is reduced from 1.05 to 0.54 V, which makes the filament grow more easily. The fluctuation of I HRS decreased from 88.88% to 49.56%. This means that the uniformity and stability of the device can be effectively improved by the plasma treatment.